Evaluation of teaching factory implementation in state vocational high schools in sleman regency - Farabbanie, Auliana; Ramadhan, Ilham; Rosidah; Arum Suryaningtyas; Pradana, Hilmy (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2026)
This study evaluates the implementation of the Teaching Factory (TeFa) program in vocational high schools (SMK) in Sleman Regency using the CIPP model (Context, Input, Process, Product). The research employed a descriptive-evaluative approach with 175 student respondents, supported by teacher input and school documents. Findings show that the curriculum has been aligned with industry needs through synchronization with partners, though limited facilities, regulations, and accessibility remain obstacles. Teachers are relatively well-prepared, most having completed industrial internships, and industry partners provide positive responses, yet disparities in infrastructure between schools are evident. The process is carried out through project-based learning with cross-major collaboration, offering realistic experiences but constrained by insufficient resources and non-standardized evaluation. In terms of outcomes, students generally display high motivation, discipline, responsibility, and technical skills, though independence and innovation remain weak. Overall, TeFa in Sleman has been on the right track to realize link and match between vocational education and industry, but improvements in facilities, evaluation standards, and innovation culture are still required Keywords: Teaching Factory, CIPP evaluation, vocational education, link and matc